Biomass to bio-ethanol: The evaluation of hybrid Pennisetum used as raw material for bio-ethanol production compared with corn stalk by steam explosion joint use of mild chemicals. (April 2016) - Zhang, Jingzhi; Song, Yanliang; Wang, Bingwu; Zhang, Xu; Tan, Tianwei
Abstract: The second generation biomass to bio-ethanol production is of growing interest. Energy crop were becoming important for second generation biomass to bio-ethanol production for their growth advantages. Hybrid Pennisetum as a new hybrid energy crop was selected as a model to compare with corn stalk. As pre-treatment methods, steam explosion and its combined action with dilute sulfuric acid, bisulfite, and mixed dilute acid and bisulfite were selected. The enzymatic hydrolysis demonstrated that the cellulose conversion is a strong function of the pre-treatment method applied, with corn stalk providing slightly better results. With dilute acid steam explosion (DA-SE), conversions were 67.6% and 54.5% for corn stalk and pennisetum, respectively. This can be attributed to the higher Cr. I of pennisetum (65.03%) than of corn stalk (54.05%). The cell lumen of pretreated pennisetum was smaller than for corn stalk as shown in SEM photos, meaning there was a substantially higher enzyme accessible surface and porosity in pennisetum, thus responsible for the higher cellulase adsorption of pretreated pennisetum . DA-SE was the most effective pre-treatment method, but the inhibitors' concentration was higher than in other methods. Combined dilute acid and bisulfite can moderately remove hemicelluloses and lignin. Cr. I values, lignin content, accessible surface and porosity were supplied the energy crop evaluation standards for bio-ethanol production. Highlights: Second generation bio-ethanol production with energy crop (hybrid pennisetum). Steam explosion pretreatment with mild chemicals. Lower inhibitor concentration. Cr. I is an important factor for enzymatic hydrolysis. Enzymatic hydrolysis reflects the pre-treatment severity.